2016
DOI: 10.7567/jjap.55.07la02
|View full text |Cite
|
Sign up to set email alerts
|

Advanced simulation technology for etching process design for CMOS device applications

Abstract: Plasma etching is a critical process for the realization of high performance in the next generation of CMOS devices. To predict and control fluctuations in the etching properties accurately during mass production, it is essential that etching process simulation technology considers fluctuations in the plasma chamber wall conditions, the effects of by-products on the critical dimensions, the Si recess dependence on the wafer open area ratio and local pattern structure, and the time-dependent plasma-induced dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 133 publications
0
12
0
Order By: Relevance
“…6 Results from a voxel-slab model, developed to investigate contact hole etching in SiO 2 , indicated that physical damage was reduced by maintaining a critical thickness of the overlaying polymer. 17,34 Bowing during the etching of HAR features was found to result from excessive fluxes of F and O radicals to the sidewalls according to the results of a line-of-sight profile simulator. 35 A model addressing pattern deformation and experimental measurements by atomic force microscopy indicated that the ratio of line width roughness to line edge roughness decreases with increasing etch depth, and the depth at which twisting occurs is shallower for a lower bias power.…”
Section: Introductionmentioning
confidence: 97%
“…6 Results from a voxel-slab model, developed to investigate contact hole etching in SiO 2 , indicated that physical damage was reduced by maintaining a critical thickness of the overlaying polymer. 17,34 Bowing during the etching of HAR features was found to result from excessive fluxes of F and O radicals to the sidewalls according to the results of a line-of-sight profile simulator. 35 A model addressing pattern deformation and experimental measurements by atomic force microscopy indicated that the ratio of line width roughness to line edge roughness decreases with increasing etch depth, and the depth at which twisting occurs is shallower for a lower bias power.…”
Section: Introductionmentioning
confidence: 97%
“…[1] Despite advancements in plasma processing, the degradation of material properties due to plasma exposure-plasma process-induced damage (PID)-has become a key issue. [2][3][4] In general, PID is classified on the basis of the mechanisms of its generation such as "physical damage," [5][6][7][8] "charging damage," [4,[9][10][11][12] and "radiation damage." [13][14][15][16][17] Physical damage is induced by high-energy ion bombardment on Si substrates or other material surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…20 Computational simulations of profile evolution in 3d have provided keen insights into fundamental processes and etch phenomena. [21][22][23][24][25][26] For example, surface roughening is a major concern in controlling CD. Guo and Sawin investigated the onset of surface roughening using a 3d cellular Monte Carlo simulation and reported that the angle of ion incidence onto the surface was a key parameter for determining the perpendicular and parallel ripples.…”
Section: Introductionmentioning
confidence: 99%
“…25 Kuboi et al investigated the time-evolution of plasma-induced damage during SiN etching in hydrofluorocarbon plasmas using a 3d voxel-slab model. 25,26 They demonstrated that the major source of silicon damage in the source/drain region was high energy hydrogen during the over-etch step.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation